Technical Evaluation, Development, and Implementation of a Remote Monitoring System for a Golf Cart - Urrea-Onate, E (IGI Global, 2016)
A technical evaluation of the sensing, communication and software system for the development and implementation of a remote monitoring system for an electric golf cart is presented. According to the vehicle s characteristics and the user s needs, the technical and economic aspects are combined in the best possible way, thereby implementing its monitoring at a distance. The monitoring system is used in two important stages: teleoperation and the vehicle complete autonomy. This allows the acquisition of video images on the vehicle, which are sent wirelessly to the monitoring station, where they are presented through a user-friendly interface. With the purpose of complementing the information sent to the remote user of the vehicle, several important teleoperation variables of a land vehicle, such as voltage level, current and speed are sensed. © 2017, IGI Global. All rights reserved.